Studi Penjadwalan Menggunakan Metode CPM dan PDM dengan Microsoft Project 2019 pada Proyek Pembangunan Pondok Darul Hijrah Putera Martapura - Marina Marina; Retna Hapsari Kartadipura (Lambung Mangkurat University Press, 2021)
In the Wisma Darul Hijrah Putera building project, a schedule was made which is expected to help the project run. For this reason, the Critical Path Method (CPM) and Precedent Diagram Method (PDM) methods are used to obtain index results from scheduling. From the results of this research analysis, it was found that the scheduling of the Wisma Darul Hijrah Putera Building Project was carried out for 64 months and 26 days with the CPM method starting on August 31, 2020 and ending on January 26, 2026 and 14 months 18 days with the PDM method starting on January 30, 2020. August 31, 2020 and ending on November 18, 2021. The big-time difference is due to differences in the use of constraints in each method.